Agglomeration Economies and Productivity Growth in Manufacturing Industry: Empirical Evidence from Indonesia - Widodo, W.; Salim, Ruhul; Bloch, Harry (Wiley-Blackwell Publishing Asia, 2014)
This study examines the effect of agglomeration economies on productivity growth in Indonesian manufacturing industries during the first decade of this century. Productivity growth is measured at the firm level using the Färe-Primont Productivity Index. Each firm's productivity growth is then regressed against a set of firm and industry characteristics, including three measures of agglomeration representing the effects of specialisation, diversity and competition. The results show evidence of a positive specialisation effect and a negative diversity effect for aggregate manufacturing and sub-sectors. Furthermore, there are mixed effects across industries, suggesting that Porter's competition externalities stimulate firm productivity growth under some conditions but not others.